2010
DOI: 10.1038/hr.2010.130
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system activity is independently associated with the risk of shift in the non-dipper blood pressure pattern

Abstract: An insufficient decrease in nocturnal blood pressure (BP) is a known factor in cardiovascular mortality. We aimed to determine whether autonomic nervous system (ANS) activity and its change over 2 years were associated with a shift to non-dipper status, independently of initial BP, in a general elderly population. From participants in the PROOF study, 600 subjects untreated for hypertension were selected (age at baseline: 65 years, men: 41.5%). Dipper/non-dipper status was defined using repeated measures of 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 27 publications
0
29
1
Order By: Relevance
“…One study reported that among HIV+ individuals, compared to HIV− individuals, resting heart rate was higher (69 vs. 57 beats per minute; p<0.001), and heart rate variation as measured by the standard deviation of normal-to-normal (SDNN) was lower (36 vs. 74 ms; p<0.01) [16]. In previous studies of the general population, autonomic and baroreflex dysfunction has been associated with masked hypertension and abnormal diurnal BP patterns [26,27]. A longitudinal study of 1011 French individuals aged 65 or older found that a standard deviation increase in very low frequency RR intervals was associated with an OR of 0.61 (95 % CI 0.41-0.91) for non-dipping BP [26].…”
Section: Autonomic Dysfunctionmentioning
confidence: 95%
See 1 more Smart Citation
“…One study reported that among HIV+ individuals, compared to HIV− individuals, resting heart rate was higher (69 vs. 57 beats per minute; p<0.001), and heart rate variation as measured by the standard deviation of normal-to-normal (SDNN) was lower (36 vs. 74 ms; p<0.01) [16]. In previous studies of the general population, autonomic and baroreflex dysfunction has been associated with masked hypertension and abnormal diurnal BP patterns [26,27]. A longitudinal study of 1011 French individuals aged 65 or older found that a standard deviation increase in very low frequency RR intervals was associated with an OR of 0.61 (95 % CI 0.41-0.91) for non-dipping BP [26].…”
Section: Autonomic Dysfunctionmentioning
confidence: 95%
“…In previous studies of the general population, autonomic and baroreflex dysfunction has been associated with masked hypertension and abnormal diurnal BP patterns [26,27]. A longitudinal study of 1011 French individuals aged 65 or older found that a standard deviation increase in very low frequency RR intervals was associated with an OR of 0.61 (95 % CI 0.41-0.91) for non-dipping BP [26]. However, it is not known whether the high prevalence of autonomic dysfunction in HIV+ individuals translates to an increase in adverse ABPM phenotypes.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…Reduced HRV was also demonstrated to predict worse cardiovascular prognosis not only in patients with coronary heart disease [6,7] and heart failure [8,9] but also in diabetic and hypertensive individuals [10,11] and in elderly population [12]. Furthermore, a reduced HRV predicted the development of hypertension in normotensive individuals [13,14] and is associated with higher odds of having a nondipping pattern in hypertensive individuals [15,16].…”
Section: Introductionmentioning
confidence: 95%
“…The polysomnographic recording was manually evaluated by an experienced physician and sleep-wake determination, sleep staging and abnormal respiratory events were defined according to standard criteria [28]. Apnoea-hypopnoea index (AHI), which indicates the number of apnoea or hypopnoea events per hour of sleep, was calculated and OSA severity was graded accordingly: no OSA (AHI 5), mild OSA (AHI 6-15), moderate OSA (AHI [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and severe OSA (AHI >30). OSA symptoms were evaluated by the Berlin questionnaire [29].…”
Section: Patients and Baseline Proceduresmentioning
confidence: 99%
“…Alteration in autonomic function plays the pivotal role in creating BPV [30] and non-dippers are characterized with an abnormal pattern of autonomic activity with higher sympathetic and lower parasympathetic modulation [31][32]. The reverse dipping state has been recognized to be related with a sympathetic activation greater for magnitude that seen in the other conditions displaying abnormalities in night-time BP pattern [33].…”
Section: Mechanism Driving Bpvmentioning
confidence: 99%